Application of heat treatment, edible coating and chemical dip as barriers to the conservation of fresh-cut vegetables (2014)
The fresh-cut vegetables consumption is increasing in the worldwide since its foray in the early 90s. The international association of fresh cut products, reported sales in 2000 of 12 billion dollars. The interest in feed quickly and healthy, has stimulated the development of vegetable fourth range, however their high metabolic activity reduces its stability and shelf life. It has promoted the adoption of technologies for minimally processed products that give them longer life and ensure the reduction of postharvest losses. In this research evaluated the effect of 3 technologies barriers on the respiration intensity and general sensory quality of six fresh-cut vegetables (broccoli (Brassica oleracea var. Italic), cauliflower (Brassica oleracea var. Botrytis), zucchini (Cucurbita pepo L.), celery (Apium graveolens), carrot (Daucus carota) and vegetable pear (Sechium edule)). Experimental design was applied in a randomized complete block, blocks made by each of the vegetables and the response variables respiration rate and general sensory quality. For the edible coating was used low methoxyl pectin 2%, 1% of carnauba wax, 1,5% glycerol and 0,05% ascorbic acid; the heat treatment was 60 °C for 2 min, adding 0,25% ascorbic acid, 0,5% citric acid and calcium chloride 0,025%; the chemical dip was carried out with a solution of 0,5% citric acid, ascorbic acid 0,05% and calcium chloride 0,05% and one control. The rate production of CO2 was measured by the static method, monitoring the gas composition of the headspace for 24 hours at 8 °C and relative humidity of 90%, the sensory evaluation of color, aroma, crispness objectionable taste were sensory characteristics taken into account in assessing the general quality of each vegetal, which was performed with a panel of 7 judges trained. It was concluded that the heat treatment and edible coating, allowed the vegetables retain the sensory quality. Statistical analysis showed no significant differences from control (p